Deletion of Bmal1 Prevents Diet-Induced Ectopic Fat Accumulation by Controlling Oxidative Capacity in the Skeletal Muscle - Wada, Taira (Int J Mol Sci, 2018)
Brain and muscle arnt-like protein 1 (BMAL1), is a transcription factor known to regulate circadian rhythm. BMAL1 was originally characterized by its high expression in the skeletal muscle. Since the skeletal muscle is the dominant organ system in energy metabolism, the possible functions of BMAL1 in the skeletal muscle include the control of metabolism. Here, we established that its involvement in the regulation of oxidative capacity in the skeletal muscle. Muscle-specific Bmal1 KO mice (MKO mice) displayed several physiological hallmarks for the increase of oxidative capacity. This included increased energy expenditure and oxygen consumption, high running endurance and resistance to obesity with improved metabolic profiles. Also, the phosphorylation status of AMP-activated protein kinase and its downstream signaling substrate acetyl-CoA carboxylase in the MKO mice were substantially higher than those in the Bmal1(flox/flox) mice. In addition, biochemical and histological studies confirmed the substantial activation of oxidative fibers in the skeletal muscle of the MKO mice. The mechanism includes the regulation of Cacna1s expression, followed by the activation of calcium—nuclear factor of activated T cells (NFAT) axis. We thus conclude that BMAL1 is a critical regulator of the muscular fatty acid level under nutrition overloading and that the mechanism involves the control of oxidative capacity.